The Stately Homes of England - Jewitt, Llewellynn Frederick William, 1816-1886; Hall, S. C. (Samuel Carter), 1800-1889 (Salt Lake City, UT : Project Gutenberg, 2016)
"The Stately Homes of England" by Llewellynn Frederick William Jewitt and S. C. Hall is a historical account written in the mid-19th century. This work explores the grandeur and significance of England's stately homes, highlighting their architectural beauty, historical backgrounds, and the notable families associated with them. It aims to illustrate and celebrate these homes, not just for their magnificence, but for the cultural and social histories they embody. The opening of this comprehensive work begins by establishing England's rich heritage of homes, seen as a source of national pride, and contrasts the sentiment of home with foreign attractions. The authors introduce Alton Towers as the first subject of their examination, emphasizing the estate's historical significance and the generosity of its owners in sharing its beauty with the public. They provide a detailed overview of Alton Towers, including its architectural features, scenic surroundings, and association with illustrious historical figures, setting the tone for a series dedicated to exploring various stately homes across England. (This is an automatically generated summary.)
Series 1. I. Alton Towers, Staffordshire. II. Cobham Hall, Kent. III. Mount Edgcumbe, Devonshire. IV. Cothele, Cornwall. V. Alnwick Castle, Northumberland. VI. Hardwick Hall, Derbyshire. VII. Arundel Castle, Sussex. VIII. Penshurst, Kent. IX. Warwick Castle, Warwickshire. X. Haddon Hall, Derbyshire. XI. Hatfield House, Hertfordshire. XII. Cassiobury, Hertfordshire. XIII. Chatsworth, Derbyshire -- Series 2. I. Belvoir Castle, Leicestershire. II. Trentham, Staffordshire. III. Knole, Kent. IV. Castle Howard, Yorkshire. V. Kedleston Hall, Derbyshire. VI. Audley End, Essex. VII. Burleigh, Lincolnshire. VIII. Hever Castle, Kent. IX. Westwood Park, Worcestershire. X. Melbourne Hall, Derbyshire. XI. Somerleyton, Suffolk. XII. Wilton House, Wiltshire. XIII. Raby Castle, Durham. XIV. Cliefden, Buckinghamshire. XV. Warnham Court, Sussex. XVI. Lowther Castle, Westmoreland. XVII. Clumber, Nottinghamshire. XVIII. Welbeck, Nottinghamshire.
Release date is 2016-02-10
E-text prepared by Giovanni Fini and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Historic buildings -- England